Alexander, who used to be rich last Sunday - Viorst, Judith; Cruz, Ray (New York : Atheneum, 1978)
Although Alexander and his money are quickly parted, he comes to realize all the things that can be done with a dollar.
Elem. School Library Collection, June 2000
School Library Journal, October 2001
Book Links (A.L.A.), March 2006
Booklist, August 2001
Horn Book, October 2009
Reference and Research Book News, September 2009
Keywords: Finance, Personal -- Fiction; Humorous stories; Personal finance -- Fiction; Humorous fiction